Synergizing Customer Satisfaction and Sustainable Innovation: Leveraging the Kano Model for Eco-Design in Product Development - Nickita, Komang (Tekmapro, 2024)
In the context of contemporary consumer demands and growing environmental consciousness, the packaging design of consumer goods has garnered significant attention for its impact on both consumer satisfaction and environmental sustainability. This paper focuses on the utilization of the Kano Model as a robust methodology for discerning pivotal attributes in sustainable cooking oil packaging design. By leveraging the comprehensive framework of the Kano Model, this research seeks to identify the essential features that not only fulfill consumer expectations but also align with environmentally responsible practices. Through a meticulous analysis of consumer preferences and environmental concerns associated with cooking oil packaging, this study aims to pinpoint the attributes that contribute to both consumer satisfaction and reduced environmental footprint. By emphasizing the synergy between consumer satisfaction and sustainable packaging, this paper underscores the vital role of the Kano Model in guiding the design process toward creating cooking oil packaging that not only meets consumer needs but also demonstrates a commitment to ecological responsibility. The insights derived from this study serve as a valuable guide for companies looking to enhance their packaging design strategies, fostering consumer loyalty while promoting sustainable practices in the cooking oil industry.